Innovative therapy, monoclonal antibodies, and beyond: Highlights from the eighth annual meeting. (December 2018) - De Santis, F.; Del Vecchio, M.; Castagnoli, L.; De Braud, F.; Di Cosimo, S.; Franceschini, D.; Fucà, G.; Hiscott, J.; Malmberg, K.J.; McGranahan, N.; Pietrantonio, F.; Rivoltini, L.; et al.
Abstract: The eighth annual conference of "Innovative therapy, monoclonal antibodies, and beyond" was held in Milan on Jan. 26, 2018, and hosted by Fondazione IRCCS–Istituto Nazionale dei Tumori (Fondazione IRCCS INT). The conference was divided into two main scientific sessions, of i ) pre-clinical assays and novel biotargets, and ii ) clinical translation, as well as a third session of presentations from young investigators, which focused on recent achievements within Fondazione IRCCS INT on immunotherapy and targeted therapies. Presentations in the first session addressed the issue of cancer immunotherapy activity with respect to tumor heterogeneity, with key topics addressing: 1) tumor heterogeneity and targeted therapy, with the definition of the evolutionary Index as an indicator of tumor heterogeneity in both space and time; 2) the analysis of cancer evolution, with the introduction of the TRACERx Consortium—a multi-million pound UK research project focused on non-small cell lung cancer (NSCLC); 3) the use of anti-estrogen agents to boost immune recognition of breast cancer cells; and 4) the high degree of functional plasticity within the NK cell repertoire, including the expansion of adaptive NK cells following viral challenges. The second session addressed: 1) the effectiveness of radiotherapy to enhance the proportion of patients responsive to immune-checkpoint blockers (ICBs); 2) the use of MDSC scores in selecting melanoma patients with high probability to be responsive to ICBs; and 3) the relevance of the gut microbiome as a predictive factor, and the potential of its perturbation in increasing the immune response rate to ICBs. Overall, a picture emerged of tumor heterogeneity as the main limitation that impairs the effectiveness of anti-cancer therapies. Thus, the choice of a specific therapy based on reproducible and selective predictive biomarkers is an urgent unmet clinical need that should be addressed in order to increase the proportion of long-term responding patients and to improve the sustainability of novel drugs.